2005
DOI: 10.1598/jaal.48.7.4
|View full text |Cite
|
Sign up to set email alerts
|

Tapping the Potential of Teacher Read-Alouds in Middle Schools

Abstract: Many educators recommend reading aloud to students, but little is known about the nature of teacher read‐aloud practices beyond elementary school. This article describes a survey of 141 middle school teachers in one U.S. school district. Eighty‐six percent of the teachers reported reading aloud to their students; however, teachers defined reading aloud in a variety of ways, including reading announcements and instructions. Many of the reasons teachers gave for reading aloud (e.g., modeling, making texts access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 9 publications
1
49
0
Order By: Relevance
“…The programme brought pupils from different schools, backgrounds and age grades together during the 2008 long vacation period. We kind of create a 'community' (Albright and Ariail, 2005) where literacy thrived and children could learn from people of other lands and far away places without having to travel there physically. We reasoned that if children that the society labels 'non-reading' are exposed to a print-rich environment and taught how to read and engage in various literacy activities, that it would have a rub-off effect on their literacy development.…”
Section: The Programmementioning
confidence: 99%
“…The programme brought pupils from different schools, backgrounds and age grades together during the 2008 long vacation period. We kind of create a 'community' (Albright and Ariail, 2005) where literacy thrived and children could learn from people of other lands and far away places without having to travel there physically. We reasoned that if children that the society labels 'non-reading' are exposed to a print-rich environment and taught how to read and engage in various literacy activities, that it would have a rub-off effect on their literacy development.…”
Section: The Programmementioning
confidence: 99%
“…However, as more and more teachers explore the power of literature across the curriculum, read alouds are increasingly being viewed as a way to promote student engagement and curriculum integration (Albright & Ariail, 2005;Laminack, 2006;Richardson, 2000;Trelease, 2006).Jen recently observed a seventh grade math teacher who uses the book The Greedy Triangle (Burns, 1995) to introduce the characteristics of polygons and to help students see examples of polygons in everyday life. Other texts used for read alouds in middle level math classrooms include Joan Bauer's Sticks (1996) and Cindy Neuschwander's (1997 Sir Cumference series.…”
Section: Start Smallmentioning
confidence: 99%
“…Johnston, 2016). However, teachers in the upper grades often read-aloud for their students (Albright & Ariail, 2005). It has been shown that reading aloud is beneficial to language growth and awareness, it increases reading motivation and gives positive experiences, expands vocabulary and offers models of various linguistic and textual structures, gives information, and helps particularly struggling readers to grasp the meaning of the text as well as to critically reflect on the text (e.g., Albright & Ariail, 2005;Clark & Andreasen, 2014;Roe 2014, 163Á165).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to all of these benefits, according to student surveys, pupils enjoy the moments of teachers reading aloud (Clark & Andreasen, 2014). Particularly L1 teachers read aloud often, especially fictional texts but also other kinds of texts (Albright & Ariail, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation